Analisis Kinerja Keuangan Pada Koperasi KSM (Komunitas Saling Membantu) Sehat Sejahtera Metro Lampung Periode 2021-2022 (International Forum of Researchers and Lecturers, 2024)
This research aims to determine the financial position analysis of the KSM Sehat Sejahtera Cooperative for the period 2021 – 2022 using Income Trend analysis. The type of data used in this research is quantitative data. The data sources according to the data obtained are primary data and secondary data as well as the documentation method with the data analysis technique used is quantitative descriptive analysis, namely a data processing method that uses mathematical calculations, which in this case uses a method namely: Income Trend. The analysis was carried out regarding Trend analysis for 1 year. From the results of the analysis for 1 year, it shows that assets and liabilities in the following year after 2021 will increase similar to what will be obtained by members who will increase.